Safety assessment of transgenic plums and grapevines expressing viral coat protein genes: New insights into real environmental impact of perennial plants engineered for virus resistance - Fuchs, M.; Cambra, Mariano; Capote, Nieves; Jelkmann, W.; Kundu, J.; Laval, V.; Martelli, G. P.; Minafra, Angelantonio; Petrovic, N.; Pfeiffer, P.; Pompe-Novak, M.; Ravelonandro, M.; et al. (2017)
The potential impact of transgenic plums and grapevines expressing viral coat protein (CP) gene constructs on the diversity and dynamics of virus populations was assessed under open and confined conditions in the frame of a research program sponsored by the European Commission. Across all field trials conducted in different locations (France, Romania, and Spain) and environments (continental and Mediterranean), transgenic plums expressing the CP gene of Plum pox virus (PPV) and transgenic grapevines expressing the CP gene of Grapevine Janleaf virus (GFLV) had no detectable effect on the emergence of recombinant PPV and GFLV species over eight-ten and three years, respectively. Also, no statistically significant difference was found in the number and type of aphids, including viruliferous individuals, and other arthropods that visited transgenic and nontransgenic plum trees. In addition, Apple chlorotic leaf spot virus, Prune dwarf virus, and Prunus necrotic ringspot virus did not influence the stability of the engineered resistance to PPV in co-infected transgenic plums over three dormancy periods. Further, under confined conditions, no recombinant virus was found to detectable level in transgenic grapevines expressing the CP gene of Grapevine virus A (GVA) or Grapevine virus B (GVB) that were challenged with the homologous or heterologous virus, despite high accumulation of transgene transcripts. Also, translocation of transgene-derived products, i.e. protein, mRNAs and siRNAs, did not occur to detectable level from transgenic grapevine rootstocks expressing the GFLV CP gene to nontransgenic scions. Altogether, our transgenic plums and grapevines expressing viral genes had a neutral impact on virus populations and non-target organisms over extended time. These findings provide new insights into the environmental impact of transgenic perennial crops engineered for virus resistance. It is expected that they will assist national and international regulatory authorities in making scientifically based decisions for the release of virus-resistant transgenic crops.